A Benchmark Test Suite for Proton Transfer Energies and its Use to Test Electronic Structure Model Chemistries - Nachimuthu, Santhanamoorthi (2012)
We present benchmark calculations of nine selected points on potential energy surfaces describing proton transfer process in three model systems, H(5)O(2)(+), CH(3)OH…H(+)…OH(2), and CH(3)COOH…OH(2). The calculated relative energies of these geometries are compared to those calculated by various wave function and density functional methods, including the polarized molecular orbital (PMO) model recently developed in our research group and other semiempirical molecular orbital methods. We found that the SCC-DFTB and PMO methods (the latter available so far only for molecules consisting of only O and H and therefore only for the first of the three model systems) give results that are, on average, within 2 kcal/mol of the benchmark results. Other semiempirical molecular orbital methods have mean unsigned errors (MUEs) of 3 to 8 kcal/mol, local density functionals have MUEs in the range 0.7 to 3.7 kcal/mol, and hybrid density functionals have MUEs of only 0.3 to 1.0 kcal/mol, with the best density functional performance obtained by hybrid meta-GGAs, especially M06 and PW6B95.